Mind the gap? Quantifying interlinkages between two traditions in migration literature - Joanna Nestorowicz; Marta Anacka (University of Warsaw, Centre of Migration Research (CMR), 2015)
Gap, split, divide are just a few among many words used in publicizing the divergence of literature on internal and international migration. In this paper we empirically test what has so far been just a conjecture. Using Web of Science data and bibliometric techniques we, first, provide quantitative measures of the size of the proclaimed gap. Second, we inquire into the existing conceptual overlap between the two strands of academic literature. Third, we search for channels through which research on internal and international migration can potentially blend into becoming a single, more holistic area of study. We find that there are significant commonalities between the two literatures when it comes to the journals where they are published, the academic disciplines they relate to, or the keywords by which they are defined. At the same time, however, it becomes visible that authors tend to remain in the realm of one domain and rarely cite papers from the other strand of literature. The latter is especially true for scientists publishing on international migration, who refer to internal migration publications only 4% of the time. In contrast, internal migration scholars have 25% of international migration papers among their citations.
Keywords: 330; citation analysis; internal migration; international migration; BibExcel; Pajek